2016
DOI: 10.1007/s13311-016-0447-1
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotection by Epigenetic Modulation in a Transgenic Model of Multiple System Atrophy

Abstract: Similar to Parkinson disease, multiple system atrophy (MSA) presents neuropathologically with nigral neuronal loss; however, the hallmark intracellular α-synuclein (αSyn) accumulation in MSA affects typically oligodendrocytes to form glial cytoplasmic inclusions. The underlying pathogenic mechanisms remain unclear. As MSA is predominantly sporadic, epigenetic mechanisms may play a role. We tested the effects of the pan-histone deacetylase inhibitor (HDACi) sodium phenylbutyrate in aged mice overexpressing αSyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…Genotyping was performed as previously described. 42 Mice of both sexes were investigated at the ages of 8 to 10 weeks (adult) and 1 year (aged). All experiments were performed according to the ethical guidelines with the permission of the Austrian Federal Ministry of Science and Research (breeding permission BMWF-66.011/0120-II/3b/2013).…”
Section: Animalsmentioning
confidence: 99%
“…Genotyping was performed as previously described. 42 Mice of both sexes were investigated at the ages of 8 to 10 weeks (adult) and 1 year (aged). All experiments were performed according to the ethical guidelines with the permission of the Austrian Federal Ministry of Science and Research (breeding permission BMWF-66.011/0120-II/3b/2013).…”
Section: Animalsmentioning
confidence: 99%
“…Gait analysis. Gait analysis was performed 10 weeks after treatment, as described previously (33). Briefly, a DigiGait Analysis System (Mouse Specifics) was used.…”
Section: Assessment Of Motor Functionmentioning
confidence: 99%
“…Such neurotoxic effects were rescued upon the treatment with an HDAC inhibitor (Kontopoulos et al, 2006 ). Another study in a mouse model of MSA showed that histone deacetylation inhibition presented a neuroprotective role in the pathogenesis of MSA-like neurodegeneration (Sturm et al, 2016 ).…”
Section: The Role Of Hdac6 In α-Synucleinopathiesmentioning
confidence: 99%